Generációs különbségekből adódó motivációs nehézségek a munkahelyeken - Visontai-Szabó Katalin (Acta Universitatis Szegediensis : forum : acta juridica et politica, 2020)
In my research I tried to find the answer to that exciting question which is in every HR experts’ mind nowadays. Namely what is the difference between the X and the Z generation in the field of work motivation. First I collected all the significant theories about how to motivate workers. The conceptions have changed a lot in the last decades but there were only slight differences as they all had a common basis, which is that people want to work, they usually love what they do. After giving a short insight to these theories, I introduce the different generations: X,Y,Z. I did not want to write about the veterans, the baby boomers and the Alpha generation as they do not play an important role on labour market anymore or so far. There have never been so big differences between the generations like now in the 21st century. The society, the culture, the economy and the technology develop with an extreme pace and it is very hard for the elderly to keep up with it. The main problem is that the HR experts, whose job is to find the proper way of motivation, are usually belong to the older generation and have no idea about what the young want. In 2019 we do not have to face with unemployment anymore, but we have to deal with the lack of workforce. This fact also affects the way how employers try to motivate their workers. Nowadays it is quite hard to find, keep and motivate people. I tried to collect the new methods and find the best practice but honestly I’m not sure that they really work. We are in the middle of a big changing and we still do not know when and how it will ends. We do not have any long term experiences about the consequences so we can only hope that they will help to find the way or else the whole labour market will collapse.